MUC16 as a Novel Target for Cancer Therapy - Aithal, Abhijit (Expert Opin Ther Targets, 2018)
INTRODUCTION: MUC16 is overexpressed in multiple cancers and plays an important role in tumorigenicity and acquired resistance to therapy. AREA COVERED: In this review, we describe the role of MUC16 under normal physiological conditions and during tumorigenesis. First, we provide a summary of research on MUC16 from its discovery as CA125 to present anti-MUC16 therapy trials that are currently in the initial phases of clinical testing. Finally, we discuss the reasons for the limited effectiveness of these therapies and discuss the direction and focus of future research. EXPERT OPINION: Apart from its protective role in normal physiology, MUC16 contributes to disease progression and metastasis in several malignancies. Due to its aberrant overexpression, it is a promising target for diagnosis and therapy. Cleavage and shedding of the extracellular domain of MUC16 is the major barrier for efficient targeting of MUC16 expressing cancers. Concerted efforts should be undertaken to target the non-cleaved cell surface retained portion of MUC16. Such efforts should be accompanied by basic research to understand MUC16 cleavage and decipher the functioning of MUC16 cytoplasmic tail. While previous efforts to activate anti-MUC16 immune response using anti-CA125 idiotype antibodies have met with limited success, neo-antigen peptide vaccines show promise for MUC16 immunotherapy.